Constitution (fundamental law) of the Union of Soviet Socialist Republics adopted at the Extraordinary eight Congress of Soviets of the USSR, December 5, 1936. (London : The Anglo-Russian New Bulletin, 1940)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: grondwet; Sovjet-Unie.